Evaluasi Kinerja Gudang sebelum dan setelah Perancangan Ulang Tata Letak: Studi pada PT Asta Nadi Karya Utama - Yoseph Sunardhi; Muhammad Dava Apriliansyah; Mora Berlianti Pangaribuan; Yohana Angelina Harefa (LPPM Politeknik Pratama, 2026)
This study aims to evaluate the effectiveness of warehouse layout redesign on operational performance at PT Asta Nadi Karya Utama. The research method employs a quantitative approach with a before-after comparative analysis design. Data were collected through structured observation and performance measurements of 30 sample items during August–September 2025. Statistical analysis results show significant improvements in all performance indicators: item retrieval time decreased by 64.4% (from 8.03 minutes to 2.86 minutes, p < 0.001, d = 2.16), inventory accuracy increased by 20.0% (from 78.5% to 94.2%, p < 0.001, d = 1.32), vertical space utilization increased by 106.8% (from 35.2% to 72.8%, p < 0.001, d = 2.15), and operator productivity increased by 127.4% (from 18.6 to 42.3 items/hour, p < 0.001, d = 1.67). These findings confirm that layout redesign through zoning system implementation and vertical space optimization significantly improves warehouse operational efficiency.